Crystal structure of N‐(1, 3‐benzothiazol‐2‐yl)‐4‐iodobenzene‐1‐sulfonohydrazide: the unexpected importance of l N‐H⋅⋅⋅π and I⋅⋅⋅π interactions on the supramolecular arrangement. Issue 17 (3rd June 2022) - Gomes, Lígia R.; Früchtl, Herbert; Low, John N.; van Mourik, Tanja; Pinheiro, Alessandra C.; de Souza, Marcus V. N.; Wardell, James L.
Abstract: The 2‐hydrazinyl‐1, 3‐benzothiazole derivatives are precursors for synthesis of several compounds of technological interest, including the Bt−NH−N=CHR1 (R1 =alkyl, aryl, heteroaryl), derivatives. Usually when Bt−NH−NH2 is allowed to react with a benzenesulfonyl chloride the substitution is observed in the terminal nitrogen of the arenehydrazine unit, but when 4‐iodophenyl sulfonyl chloride (4‐IC6 H4 SO2 Cl) was used, the product isolated was the title compound as confirmed by Rx‐analysis. Determination of the crystal structure revealed that the definition of the arrangement was driven by N−H⋅⋅⋅π, C−I⋅⋅⋅π and S2−O21⋅⋅⋅π interactions instead of the classic O⋅⋅⋅H−N hydrogen bonds. The interactions were confirmed by HS analysis. Interaction energy calculations showed that the π interactions‐based motifs play an important role in the supramolecular arrangement, contributing about 60 % to the total energy of the lattice. DFT calculations showed that the energy of the C−I⋅⋅⋅π dimer is complemented with contributions of π⋅⋅⋅π stacking and N−H⋅⋅⋅π interaction between the primary amine and the thiazole aromatic ring. Abstract :